The 5th International Congress of CiiEM (IC CiiEM) 2021
DOI: 10.3390/msf2021005002
|View full text |Cite
|
Sign up to set email alerts
|

Cohesiveness of Powdered Co-Amorphous Olanzapine and Impact on Tablet Production

Abstract: The evaluation of the processability of co-amorphous mixtures is of paramount importance since these systems are increasingly used to address the poor solubility presented by most of the drugs in research and development. This work shows that co-amorphous olanzapine powders present higher cohesiveness than their crystalline counterpart and resulted in the production of tablets with a higher tensile strength and a slower release of the drug. As a result, this work demonstrates that despite the solubility advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
3
3
0
Order By: Relevance
“…Inversely, the addition of SAC to OLZ-containing formulations resulted in a substantial enhancement of the crushing strength of pellets (p < 0.01, by comparison with pellets containing OLZ in the matrix) (Table 2). These results are in line with previous publications which reported that tablets containing CAMs presented higher crushing strength values, as compared to those prepared using the respective crystalline counterparts [27,28,50]. This may be explained by the higher cohesiveness of OLZ in the CAM form [27,28,50] which may have increased the number and/or intensity of bonds established in the matrix of pellets.…”
Section: Preparation Of Pellets Containing Olanzapine In the Matrixsupporting
confidence: 92%
See 2 more Smart Citations
“…Inversely, the addition of SAC to OLZ-containing formulations resulted in a substantial enhancement of the crushing strength of pellets (p < 0.01, by comparison with pellets containing OLZ in the matrix) (Table 2). These results are in line with previous publications which reported that tablets containing CAMs presented higher crushing strength values, as compared to those prepared using the respective crystalline counterparts [27,28,50]. This may be explained by the higher cohesiveness of OLZ in the CAM form [27,28,50] which may have increased the number and/or intensity of bonds established in the matrix of pellets.…”
Section: Preparation Of Pellets Containing Olanzapine In the Matrixsupporting
confidence: 92%
“…These results are in line with previous publications which reported that tablets containing CAMs presented higher crushing strength values, as compared to those prepared using the respective crystalline counterparts [27,28,50]. This may be explained by the higher cohesiveness of OLZ in the CAM form [27,28,50] which may have increased the number and/or intensity of bonds established in the matrix of pellets.…”
Section: Preparation Of Pellets Containing Olanzapine In the Matrixsupporting
confidence: 92%
See 1 more Smart Citation
“…Unfortunately, the high cohesiveness of extrudates containing OLZ and SAC prevented the production of pellets. The cohesiveness of OLZ-CAM was described previously [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…To increase the stability of amorphous OLZ, co-amorphization of the drug with saccharin (SAC) has been attempted [ 35 ]. Unfortunately, the co-amorphization of OLZ resulted in a cohesive and non-free-flowing powder, impairing its handling per se (tableting or capsule filling) into dosage forms [ 36 , 37 ] and requiring the use of further down-streaming processing to overcome these drawbacks.…”
Section: Introductionmentioning
confidence: 99%